Local elasticity of the aorta in patients with type 2 diabetes mellitus. Issue 9 (September 2020) - Dec-Gilowska, Małgorzata; Trojnar, Marcin; Makaruk, Bogusław; Mosiewicz-Madejska, Barbara; Dzida, Grzegorz; Mosiewicz, Jerzy
Objective: Arterial elasticity is important for assessing the state of an artery. This cross-sectional study aimed to non-invasively examine stiffness parameters of the ascending aorta in patients with type 2 diabetes mellitus (T2DM). Methods: We studied 58 patients, including 38 with T2DM and 20 controls. The stiffness of the aorta was evaluated during transthoracic echocardiography. Aortic parameters of stiffness, such as the stiffness index, elasticity index, and compliance index, were calculated using the aortic maximal diameter, aortic minimal diameter, and blood pressure. Results: Pulse pressure values were significantly higher patients with T2DM than in controls. The β index was significantly higher in patients with T2DM lasting for >7 years compared with those with T2DM lasting for <7 years. Mean aortic compliance was significantly lower in patients with a longer duration of diabetes than in those with a shorter duration of diabetes. Aortic elasticity was significantly lower in patients with diabetes and arterial hypertension compared with patients without diabetes with concomitant arterial hypertension. Conclusions: Patients with T2DM, especially when T2DM is long-term, have increased stiffness and decreased compliance of the ascending aorta. Pulse pressure, which is a cardiovascular risk factor, is also significantly increased in patients with T2DM.